Greening transport activities in the food retail supply chain. Issue 1 (2016) - Petljak, Kristina; Renko, Sanda; Rasic, Sanda
From an operations perspective, retailers are seeking to manage and improve relationships with their customers, brand image, customer services, etc., in order to underline their green potential, because literature has considered green and sustainable business practices as a means to reducing costs. Among different retail operations and activities, transport has caused the highest costs and has been insufficiently investigated as well. The main purpose of this paper is to investigate the greening of the transport activities in the food retail supply chain and characteristics of the food retailers' who are leaders in pursuing such activities. In such a way, the paper reveals the impact of food retailers' green initiatives on the way they manage their transport and logistics services. For the purpose of the paper, a quantitative study on the sample of 190 food retail companies operating on the Croatian market was conducted. The results suggest that generally retailers see green transport and other logistical activities as an overall positive activity in terms of reducing costs and beyond, however usage of such green practices still differs a lot among observed food retailers.